SUMMER DIURNAL CYCLE AT DOME C ON THE ANTARTIC PLATEAU - Barral, Hélène; Vignon, E; Bazile, Eric; Traullé, Olivier; Gallée, Hubert; Genthon, Christophe; Brun, Christophe; Couvreux, Fleur; Le Moigne, Patrick (HAL CCSD, 2014)
International audience The ice-sheet offers us ”laboratory cases” with endless snow covered, relatively homogeneous, flat or sloped areas with persistent and strong stable stratifications resulting in low level jets. Dome C (75°06 S,123°E) on the East Antarctic Plateau is one of them.